Philippine Public Secondaryy Economics Teachers’ Level of Competence and Problems Felt in Terms of Curriculum Content, Instruction, and Assessment and Evaluation Procedures - I. Cabauatan, Jr, Leonardo; M. Dacles , Darwin Don (Future Science / FSH-PH Publications, 2021)
This quantitative-qualitative research study investigated the level of competence of 44 Economics Education teachers from Area IV of the Division of Isabela and to the Division of Santiago City as a separate chartered school’s division in the province. Specifically, it aimed to study the competence level of economics teachers across curriculum content, instructional design and implementation, and assessment and evaluation procedures. Likewise, it further investigated the prevailing problems encountered and felt by the teacher-respondents in teaching economics. The respondents took an examination, and answered a researcher-made survey-questionnaire to measure and determine their competence level in economics in terms of the abovementioned three educative process. The findings revealed that the economics teachers have low competence in terms of curriculum content knowledge. Further, the result shows the teacher-respondents have lack of knowledge about the subject-matter, hence, are not competent in terms of dealing with fundamental concepts in economics education. Moreover, vague concepts and textual errata were also encountered in learning materials which ultimately create misconceptions throughout the teaching-learning process. Besides, the economics teachers are competent in teaching economics in terms of instructional design and implementation and assessment and evaluation procedures. They are proficient enough in executing the lessons in economics, however technical problems like unavailability of materials, too advance learning competency and instructional activities infused in learning materials, poor results of academic performance, lack of knowledge and orientation on the use of ICT-based teaching and the like are some of the problems that challenges their competence in teaching the subject. The key findings and results of the study provide implications for further studies about other factor variables that implicates teaching competence of economics teachers.